ANALISYS OF THE COMPOSITION OF THE CATCH FISHING ROD BACK AND FORTH USING A DIFFERENT BAIT IN THE WATERS BUNGUS OF WEST SUMATRA PROVINCE - EDO Dwi PURNOMO; Pareng Rengi; Bustari ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis study was conducted in May 2014 Bungus waters of West Sumatra province.This study aims to determine the composition of the catch rod back and forth as a whole (kg),the type and amount of catches (tail) using different baits in PPS Bungus West Sumatraprovince. The method used in this study is a survey method. The results were obtainedcontained the highest number of catches in squid bait fish with a weight of up to 12 588 kg,bait fish as much as 4 tails Layur weighing 188 kg, fly fishing lures 2 tails weighing 91 kg.Based on the type of fish caught during the study was the fish Layur(Trichiuruslepturus),marlin / meka(Makairaindica), Tongkol (Euthynnus affinis), big eye tuna (Thunnusobesus)and yellowfin tuna (Thunnusalbacares).Keywords: Fishing stalling, bait, catches